The Excited Electronic States and the Oscillator Strenght Calculated for Flattened Cylindrical Cd1-Xznxs Quantum Dots - Marzougui, S; Safta, N (International Journal of Chemistry and Materials Research, 2015)
The present paper is aimed to investigate theoretically the quantum confinement in Cd1-xZnxS – related quantum dots with x the atomic fraction of Zn. For both electrons and holes, we have calculated the excited bound states with use of the flattened cylindrical geometry model and assuming a finite potential at the boundary. The confined sub bands have been calculated based on squared quantum well wave – functions. A theoretical analysis is also made to calculate the oscillator strength of inter sub band transitions as a function of zinc composition. The goal of the latter study is to investigate the optical behavior of flattened cylindrical Cd1-xZnxS quantum dots.